Refractory tertiary hyperparathyroidism after calcimimetics and delayed parathyroidectomy in a kidney transplant recipient - Ekamol Tantisattamo; David D. Ono (The Korean Society of Nephrology, 2012)
Persistent hyperparathyroidism affects renal outcomes and mortality. After kidney transplantation, cinacalcet is not approved as treatment for hyperparathyroidism. Parathyroidectomy, on the other hand, reverses electrolytes and mineral bone metabolism in almost all cases. Early parathyroidectomy may increase the chance of resolving hyperparathyroidism. A 58-year-old man with ESRD status post deceased donor kidney transplantation 3 years prior presented with bone aches. He had persistent hypercalcemia and hypophosphatemia secondary to hyperparathyroidism. Serum calcium ranged 9.3-11.4 mg/dl and serum phosphorus was decreased with a lowest value of 2.1 mg/dl. Intact PTH level was elevated to 487 pg/ml and total 25-OH vitamin D was 20 ng/ml. Bone density studies indicated osteopenia. He refused parathyroidectomy and was treated with cinacalcet. Because of persistent hyperparathyroidism, he underwent subtotal parathyroidectomy. Postoperatively, he required high phosphorus diet, phosphate supplements, and cinacalcet to maintain normal serum phosphorus levels. Intact PTH was still elevated with the level of 188 pg/ml while he continued cinacalcet. Normally, parathyroidectomy is performed 1 year posttransplantion unless severe bone disease, refractory hypercalcemia, or difficulty controlling phosphate wasting occurs. Phosphate wasting from hyperparathyroidism in our patient indicated parathyroidectomy; however, the surgery was delayed for 3 years while cinacalcet had been used. Post parathyroidectomy, hyperparathyroidism still persisted. Both cinacalcet and parathyroidectomy are imperfect to reverse hyperparathyroidism. Timely parathyroidectomy may determine the reversal of electrolyte and metabolic bone diseases; however, a delayed procedure may not have the same benefit. Since hyperparathyroidism is associated with higher incidence of kidney allograft dysfunction and postoperative mortality, should there be a level where pretransplant parathyroidectomy is performed?